Neuroimaging in Evaluation of Migraine Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The utility of neuroimaging in the evaluation of children with migraine and chronic daily headache, with normal neurologic examination, was determined by a retrospective review of 302 patients, aged between 6 and 18 years, seen in the Pediatric Neurology Clinic, Children's Hospital, Eastern Virginia Medical School, Norfolk, 1997-1999.